RANCANG BANGUN DAN ANALISA UNJUK KERJA SISTEM PENGAWASAN DENGAN FRAME RATE DINAMIS BERDASARKAN DETEKSI PERGERAKAN - Stephanie Imelda Pella (Jurnal Media Elektro, 2021)
Designing the Internet of Things (IoT) based surveillance systems is usually a trade of the frame rate in the video streaming to capture any movement in the frame and the bandwidth needed to stream the video. This research proposes a way to achieve bandwidth efficiency while still stream in a required frame rate by implementing video streaming with a dynamic frame rate based on movement detection. The system comprises surveillance devices; each consists of a Raspberry Pi single-board computer connected to a camera, and a central web server that mainly handles user authorization. The system was developed using Motion server, MySQL database engine, and PHP programming language. A system measurement using Wireshark network analyzer is used to evaluate key parameters of the system such as bandwidth requirement, round trip time delay, and error packet. The result shows that using a system with a dynamic frame rate requires as little as 25% bandwidth compared to the system with fix framer rate.